ANALISIS KECEPATAN RATA-RATA WAKTU DAN KECEPATAN RATA-RATA RUANG PADA JALAN ARTERI - Sianturi, Fenny Novita Meysabed (Universitas Medan Area, 2024)
Dr. Mansyur Street is a road that supports educational, office, and trade activities and traveled by passenger cars, motorbikes, large buses, and other heavy vehicles. When traffic volumes are high during rush hours, roads become transportation infrastructure that is clearly unable to accommodate the flow of traffic. Traffic jams result in limited vehicle movement, thereby reducing vehicle velocity. Because of the traffic congestion problems occurring on this road section, an analysis is needed to determine the actual speed. In this study, primary data is collected specifically for time mean speed and space mean speed. Based on the results of data processing's results and analysis on the Dr. Mansyur Road section, it can concluded that the time mean speed and space mean speed are not by the speed limits. The TMS and SMS values are below 30 kilometers per hour while the speed limits value according to the road function is 30 kilometers per hour. The traffic congestion that occurs results in limited vehicle movement thereby reducing vehicle speed.